Augmented Reality in Education: A Meta-Analysis Of (Quasi-) Experimental Studies to Investigate the Impact - Hunaepi, Hunaepi; Sudiatmika, A.A Istri Agung Rai; Fadly, Wirawan (Reflection Journal, 2023)
The objective of this study is to thoroughly examine the influence of AR on educational achievements by amalgamating findings from (quasi) experimental investigations. This study constitutes a meta-analysis approach, which involves analyzing previous research statistically. Specifically, it focuses on 15 articles meeting the determined criteria for data inclusion in this meta-analysis, encompassing: 1) Research Methodology: Restricted to studies carried out via experimental or quasi-experimental designs, 2) Pertinence to Research Variables: Emphasizing research directly investigating AR's impact on educational achievements, 3) Indexing: Inclusion of publications indexed by reputable databases like SINTA, DOAJ, Copernicus International, or Scopus. Statistical Measurements: Encompassing studies providing relevant statistical metrics ('r' and 't') concerning the relationship between the variables studied. The outcomes demonstrate that the evidence indicates a beneficial effect of AR in augmenting educational outcomes. This deduction is drawn from a considerable average estimated Effect Size (1.231) alongside an exceedingly low p-value (< 0.001), denoting a highly significant statistical association between AR and heightened educational achievements. Although the collective findings strongly support AR's advantageous impact on various educational aspects, further research is imperative to address acknowledged limitations and optimize the potential of AR technology in enhancing educational achievements, motivation, and engagement across diverse educational settings and student cohorts.